Estudo dos efeitos tóxicos causados pela exposição à micro/nanopartículas de tereftalato de polietileno (PET) ao longo do desenvolvimento de zebrafish (Danio rerio) - Teodoro, Lilian de Souza (2022)
Currently, Polyethylene Terephthalate (PET) is one of the most used thermoplastics in the plastics industry. The good moldability and thermal stability allow the application in the production of food and beverage packaging, pharmaceutical and cleaning products, in addition to the applied use in the textile industry. However, the hydrophobic characteristic and the rigidity of the polymeric chain of PET prevent its decomposition when improperly disposed of in the environment. Under these conditions, every year a considerable amount is released into landfills or natural environments, where they are continuously fragmented into smaller particles called microplastics (MPs > - 5 mm) and nanoplastics (NPs - 100). The availability of these particles in different ecosystems generates the imminent risk of ingestion or penetration into living organisms. Although there are some good studies evaluating behavior and the effects of exposure to MPs and NPs, the process is far from being understood. In this work, we performed the chemical degradation of PET using trifluoroacetic acid, to evaluate the effects of exposure to different concentrations (0.5, 1, 5, 10, 20 mg/L) of PET MPs and NPs on morphological, functional parameters, behavioral and biochemical factors in the early stages of zebrafish (Danio rerio) development. The characterization of the degraded PET indicated that MPs (1.305 ± 2.032 μm) and NPs (109 ± 518 nm) were generated. After six days of exposure our results indicate that MPs and NPs from PET can reduce spontaneous tail curl (STC), increase heart rate, accumulate on the chorion of embryos and reduce the distance between the eyes. Although our results suggest that exposure to PET MPs and NPs under the conditions tested is not very toxic to the early stages of zebrafish development, it is very important that further studies testing other conditions are carried out.